2010
DOI: 10.1111/j.1099-0860.2009.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Perspectives on their Economic Activity as a Pathway to Resilience

Abstract: When viewed in the context of children’s physical, social, and economic ecologies, children’s work has both contextually specific benefits and consequences. This paper examines children’s experiences of their economic activity using a theory of resilience as a contextually and culturally embedded phenomenon [British Journal of Social Work, 38 (2008) 218]. Though there is evidence that child labour is a potential threat to children’s well‐being, some forms of children’s work may function as potential sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 55 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…That position contradicts the dominant discourse in Brazil which labels all child labor as exploitive (ILO 2007;Pyl 2010) even though other qualitative studies of working children have shown that children can derive benefits from their work experience (Libório and Ungar 2010). While we could find instances where children argued that their work was protective, the theme of protagonism helped to explain why they experienced it in that way.…”
Section: Domains Descriptionmentioning
confidence: 69%
See 1 more Smart Citation
“…That position contradicts the dominant discourse in Brazil which labels all child labor as exploitive (ILO 2007;Pyl 2010) even though other qualitative studies of working children have shown that children can derive benefits from their work experience (Libório and Ungar 2010). While we could find instances where children argued that their work was protective, the theme of protagonism helped to explain why they experienced it in that way.…”
Section: Domains Descriptionmentioning
confidence: 69%
“…Specifically, this study focused on identifying otherwise hidden coping strategies that working children in Brazil use to effectively maintain well-being in an environment where child labor is tolerated by economically disadvantaged families even though it is legally prohibited (Libório and Ungar 2010;Schawartzman and Schawartzman 2004). Among the strategies that emerged during analysis of the study's data was a process we labeled 'resilience as protagonism.'…”
Section: Protagonism As a Cultural Practicementioning
confidence: 99%
“…To illustrate, these include the controversial perspectives of working children who say they prefer work over school as a means of securing their future (Liborio and Ungar, 2010;Liebel, 2004) or some adult victims of sexual abuse who argue it is better to not report their abuse if doing so threatens their social status within their community (The Working Group on Child Sexual Abuse, 1996). Arguably, such nuanced understandings of resilience processes can remain invisible unless they are documented and then shared in ways that give them credibility, even if they represent pathways to wellbeing for only a small group of people coping in a particularly disadvantaged context.…”
Section: Researching Resilience Across Cultures and Contextsmentioning
confidence: 98%
“…Many studies of youth in economic and political contexts of poverty, injustice, and social oppression show that young people who survive best are those who exploit opportunities that are available to them, even if their patterns of behavior (e.g., delinquency, early school leaving) appear to further disadvantage them (Bottrell, 2009 ;Ng-Mak, Salzinger, Feldman, & Stueve, 2010 ) . For example, gang involvement may be protective to the child without other means of feeling secure in his community (Taylor et al, 2002 ) ; alcohol use (Ziervogel, Ahmed, Fisher, & Robertson, 1997 ) , or early sexual initiation may be preferred as rites of passage into adulthood (Mof fi tt, Caspi, Rutter, & Silva, 2001 ) ; children's participation in the labor force may bring with it social and economic gains that exceed what they can expect at school (Liborio & Ungar, 2010 ) . It is important to note that the CYRM does not distinguish between prosocial and non-normative means of accessing personal and social resources.…”
Section: Clinical and Community Applications For An Ecological Measurmentioning
confidence: 99%